Parametric Study for the Effect of Suspension Composition on Electrophoretic Deposition of Zirconia (Journal of University of Babylon for Engineering Sciences, 2018)
Electrophoretic deposition (EPD) is continued to be a major activity of science and technology in view of its advantages of controlling the deposit thickness, morphology, and microstructure. The method enables the formation of films on substrates of complex geometry that suits for various applications including biomaterials. However, the method involves controlling of various process parameters, which are of vital effects on the properties of the deposit.Besides, deposition of zirconia nano particles is vital for production of parts used in restorative dentistry. This work was a study the effect of polyethylene glycol polymer as a binder-suspension agent, the amount the solid loading (zirconia particles), and the effect of the toluene as a dielectric liquid, on the final thickness and green density of the deposed parts.